Kontribusi konsep diri terhadap perencanaan karier siswa - Dian Rahmawati; Rezky Permata Sari; Afiatin Nisa (Universitas Indraprasta PGRI, 2022)
career planning was an important component in students' career development. One thing that is thought to have an effect on students' career planning is self-concept. The aim of this study was to determine whether self-concept affects the career planning of SMKS Muhammadiyah 11 Jakarta students. The research is a quantitative research with a survey type. The population in this study were 394 students. The sample was drawn by simple random sampling with a sample size of 39 students. Data were collected through a questionnaire. Data were analyzed using simple linear regression test. The results showed that a). Students' self-concept is in the medium category, b) students' career planning is in the high category, and c) self-concept has a significant effect on career planning of students at SMKS Muhammadiyah 11 Jakarta